Body composition as a predictor of chemotherapy-related toxicity in ovarian cancer patients: A systematic review - Rizzo, Stefania; Raia, Giorgio; Del Grande, Maria; Gasparri, Maria Luisa; Colombo, Ilaria; Manganaro, Lucia; Papadia, Andrea; Del Grande, Filippo (Frontiers in Oncology, 2022)
Objectives: the main objective of this systematic review was to examine the literature evaluating association of image-based body composition with chemotherapy-related toxicity in ovarian cancer patients. A secondary objective was to evaluate the different definitions of sarcopenia across studies. Methods: This systematic review was conducted according to the PRISMA-DTA statement and the protocol was registered on Prospero. A comprehensive literature search of 3 electronic databases was performed by two authors. For each eligible article, information was collected concerning the clinical setting; basic study data; population characteristics; technical aspects; body composition features; chemotherapy drugs administered; association of body composition values and toxicities. The overall quality of the included studies was critically evaluated. Results: after the initial retrieval of 812 articles, the systematic review included 6 articles (5/6 studies were retrospective; one was prospective). The number of patients ranged between 69 and 239; mean/median age ranged between 55 and 65 years; the percentage of sarcopenic patients ranged between 25% and 54%. The cut-off values to define sarcopenia and the vertebral levels for evaluation of body composition were different. Five studies included chemotherapy based on carboplatin and paclitaxel, 1 included chemotherapy based on pegylated liposomal doxorubicin. Among the studies including carboplatin and paclitaxel, 3/5 demonstrated an association with toxicity, whereas 2/5 did not. Altogether, 4/6 papers demonstrated an association between the body composition values and the development of chemotherapy-related toxicities. Conclusions: there is a wide variability of results about the association of body composition and chemotherapy-related toxicity in ovarian cancer patients. Therefore further studies, possibly including a comprehensive assessment of body compartments and where the definition of body composition cut-offs is constant, are warranted to better understand this association.